40.3k views
1 vote
Hi I need help every answer that was given to me was wrong as well as the explanation please help

Hi I need help every answer that was given to me was wrong as well as the explanation-example-1
User Tetar
by
4.3k points

1 Answer

4 votes

Answer:

Step-by-step explanation:

If we reflect a coordinate, (x, y) over the y axis, the sign of the y coordinate remains the same while the sign of the x coordinate reverses. From the information given,

The coordinates of the original triangle are

D(3, 6), E(- 4, - 3), F(6, 1)

The coordinates of the image are

D'(1, 6), E'(8, - 3), F'(- 2, 1)

Also, if a coordinate is reflected over the line, x = k, the new coordinates would be

(2k - x, y). Let us assume that k = 2. By reflecting the line over x = 2, we have the following coordinate

For D(3, 6), the new coordinate is

(2 * 2 - 3, 6) = (4 - 3, 6) = (1, 6)

For E(- 4, - 3), the new coordinate is

(2 * 2 - 4, - 3) = (4 - - 4, - 3) = (8, - 3)

For F(6, 1), the new coordinate is

(2 * 2 - 6, 1) = (4 - 6, 1) = (- 2, 1)

We can see that the coordinates match the ones stated. Thus, the reflection rule is

A reflection over the line, x = 2

User Xavier DSouza
by
4.8k points